An overview of Turkey's waste tire problem - Şen, Nejdet; Demir, Caner; Demirbaş, Ayhan (SILA SCIENCE, 2012)
This study was performed in order to be in the quality as a forecasting about explanation of the situation of waste vehicle tires in Turkey and the studies related with them. An analysis was carried out about which developments were provided in Turkey related with waste tires until now and will light the way for future studies
Keywords: Turkey's waste tire problem; Waste; Waste tire; Waste tire pyrolysis; Waste tire recycling